2009
DOI: 10.4314/wajae.v9i1.45676
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural and synthetic soil conditioners on soil moisture retention and maize yield

Abstract: The efficacy of a natural soil conditioner, Coco-Peat (C-P), and synthetic soil conditioners, Terawet (T-200) and Teraflow (T-F), in improving soil moisture content were examined on five Ghanaian soil series (Akroso, Akuse, Amo, Hake and Oyarifa). In general, the water retention of T-200 and C-P treated soils were similar but significantly higher (p < 0.001) than that of T-F and the control (C-T) treated soils, which were also similar on all the test soils. The dry matter yields of the test crop (maize) were 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 9 publications
3
26
0
Order By: Relevance
“…Synthetic soil conditioners also possess great potential for restoring soil productivity where the opportunity for irrigation is limited. It has been found that the water storage at different tensions improved significantly in sandy soil treated with gel conditioner (Abedi-Koupai et al, 2008;Choudhary et al, 1995;Huttermann et al, 1999;Yangyuoru et al, 2006). It was also reported that the use of hydrogel increased the amount of available moisture in the root zone, resulting in longer intervals between irrigations (Abedi- Koupai et al, 2004;Allahdadi et al, 2005;El-Hady et al, 2009;Flannery and Busscher, 1982;Sharma, 2004).…”
Section: Introductionmentioning
confidence: 87%
“…Synthetic soil conditioners also possess great potential for restoring soil productivity where the opportunity for irrigation is limited. It has been found that the water storage at different tensions improved significantly in sandy soil treated with gel conditioner (Abedi-Koupai et al, 2008;Choudhary et al, 1995;Huttermann et al, 1999;Yangyuoru et al, 2006). It was also reported that the use of hydrogel increased the amount of available moisture in the root zone, resulting in longer intervals between irrigations (Abedi- Koupai et al, 2004;Allahdadi et al, 2005;El-Hady et al, 2009;Flannery and Busscher, 1982;Sharma, 2004).…”
Section: Introductionmentioning
confidence: 87%
“…Under deficit water availability, recent water management techniques, viz. precise irrigation scheduling, fertigation, and use of superabsorbent polymers with high water holding capacity, bio-compatibility, and synthetic flexibility raise new hopes to enhance crop productivity and WUE under declining water resources by improving water relations in sandy soils ( Seliktar, 2012 ; Dai et al., 2017 ; Yangyuoru et al., 2006 ). Under limited irrigation water availability, the use of synthetic polymers improves water availability to plants by restricting the drainage of water beyond the root zones ( Narjary et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized as having large sorption and ion-exchange capacity, ion-exchange selectivity, properties of a molecular sieve, catalytic activity, and structural thermal stability at temperatures of up to 700–750°C. Zeolites do not easily break down over time and therefore, they remain in the soil to improve nutrients retention [ 12 ]. Besides, their hydrated amorphous silica skeleton are able to retain water and beneficial nutrients in the root zone and significantly reduce water and fertilizer costs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%